1997
DOI: 10.1002/etc.5620160924
|View full text |Cite
|
Sign up to set email alerts
|

Tadpole swimming performance and activity affected by acute exposure to sublethal levels of carbaryl

Abstract: Abstract-General activity and swimming performance (i.e., sprint speed and distance) of plains leopard frog tadpoles (Rana blairi) were examined after acute exposure to three sublethal concentrations of carbaryl (3.5, 5.0, and 7.2 mg/L). Both swimming performance and spontaneous swimming activity are important for carrying out life history functions (e.g., growth and development) and for escaping from predators. Measured tadpole activity diminished by nearly 90% at 3.5 mg/L carbaryl and completely ceased at 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
105
2
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(110 citation statements)
references
References 36 publications
1
105
2
2
Order By: Relevance
“…Larval amphibians alter their behavior in response to their biotic and abiotic environment (39,40). Different densities of conspecifics or the presence of other species may alter behaviors such as schooling or foraging, which could change their likelihood of encountering Bd or transmitting it to other individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Larval amphibians alter their behavior in response to their biotic and abiotic environment (39,40). Different densities of conspecifics or the presence of other species may alter behaviors such as schooling or foraging, which could change their likelihood of encountering Bd or transmitting it to other individuals.…”
Section: Discussionmentioning
confidence: 99%
“…LC50 estimates have been extremely useful in determining the relative lethality of different pesticides and the relative susceptibility of different organisms. However, the lethality of very low concentrations of pesticides (Ͻ ϽLC50) is often unknown (12,13).…”
mentioning
confidence: 99%
“…Whereas myriad tests of carbaryl toxicity have been conducted on birds, mammals, fish, and invertebrates, there are few published studies on amphibians. Past studies of amphibian responses to carbaryl have found that carbaryl reduces tadpole activity and growth, and LC50 estimates vary between 2.5 and 20.6 mg͞liter (12,13,15,23).…”
mentioning
confidence: 99%
“…Pesticides are well known to affect amphibians (Bridges 1997;Brunelli et al 2010;Davidson 2004, Howe et al 2004Paganelli et al 2010;Relyea 2005a;Relyea 2005b;Relyea et al 2005). Though effects on individuals do not necessarily impair population viability (Forbes and Calow 2002;Rohr et al 2006;Schmidt 2004), an ultimate deterioration cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%